Saba' islamic portal system (Book online ordering system) - Muhammad Zulfaris, Mohd Salleh (2011)
Saba' Islamic Portal System (SIPS) functioned as a Book Online Ordering System that specialized as a portal for business part. Besides that, it also have some features in order to make sure it can have multi functions. In addition, through Book Online Ordering System, the users registered can buy books via online without going to book store anymore. The idea to build the Book Online Ordering System is parallel with the current situation that internet has widely used and already become a lifestyle for everyone. In order to build the system, waterfall model is used. It has 5 steps or stages there are Planning that come out with Software Development planning(SDP), Requirement that will come out with Software Requirement System (SRS), Design that will come out with Software Development Design(SDD), Implementation that will come out with the system, Testing and Maintenance. The system will use PHP and html language. For storing data, MySql to be used. Hopefully,the Saba' Islamic Portal System (Book Online Ordering System) can beome the best portal in book online ordering system.